Menstrual blood-derived stromal cells: insights into their secretome in acute hypoxia conditions - María Ángeles de Pedro; María Pulido; Verónica Álvarez; Federica Marinaro; Ana María Marchena; Francisco Miguel Sánchez-Margallo; Javier G. Casado; Esther López (BMC, 2023)
Abstract Background Despite constant advances in regenerative medicine, the closure of chronic wounds is still challenging. Therapeutic approaches using locally administered MSCs have been considered a promising option. However, the viability of these cells is seriously threatened by acute hypoxic stress linked to wound healing. In this work, we aimed to study the tolerance of Menstrual blood-derived stromal cells (MenSCs) to acute hypoxia and their therapeutic paracrine effect. Methods Isolated MenSCs were phenotypically characterized and evaluated in terms of proliferation, viability, and gene expression, under acute hypoxia (AH) compared with conventional cultured condition or normoxia (N). A step further, the secretome of MenSCs under acute hypoxia was analyzed with respect to their miRNAs content and by in vitro functional assays. For the analysis of differences between the two groups, Student's t-test was performed and one-way ANOVA and Tukey's multiple comparisons test for multiple groups were used. Results Our results revealed that the viability of MenSCs was not affected under acute hypoxia, although proliferation rate slowed down. Gene analysis revealed 5 up-regulated (BNIP3, ANGPTL4, IL6, IL1B, and PDK1) and 4 down-regulated genes (IDO1, HMOX1, ANGPTL2, and HGF) in AH compared to N. Global gene expression analysis revealed a decrease in the gene ontology functions of migration and wound response with respect to the normoxic condition. In contrast, functions such as angiogenesis were enriched under the AH condition. Regarding the secretome analysis, two miRNAs involved in angiogenic processes (hsa-miR-148a-3p and hsa-miR-378a-3p), were significantly up-expressed when compared to the normoxic condition, being MYC gene, the unique target of both. Functional assays on HUVECs revealed a potential pro-angiogenic capacity of MenSCs cultured in both oxygen conditions (N and AH) based on the wound closure and tube formation results of their released paracrine factors. However, when compared to normoxia, the paracrine factors of MenSCs under acute hypoxia slightly reduced the proliferation, migration, and in vitro wound closure of HUVECs. Conclusions MenSC exhibited a good survival capacity under acute hypoxic conditions as well as beneficial properties applicable in the field of tissue regeneration through their secretome, which makes them a potential cell source for wound healing interventions.